2018
DOI: 10.4103/jlp.jlp_37_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3-(4,5-dimethylthiazol- 2-yl)-2,5-diphenyl tetrazolium bromide method for assessing biofilm formation in vitro by Trichosporon spp.

Abstract: BACKGROUND: Invasive infections due to Trichosporon spp. have increased recently and are frequently associated with indwelling medical devices. Such infections which are associated with biofilm formation do not respond to the routinely used antifungal agents and are often persistent, associated with high mortality rate. Various methods have been described by researchers to evaluate and quantify the biofilm formation. AIM: This study was conducted to compare two methods of biofilm production by Tricho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Studies that assessed correlation between CV and MTT methods have reported conflicting results. Although some studies found that the CV assay was positively correlated with MTT [67][68][69], other studies did not [70][71][72].…”
Section: Discussionmentioning
confidence: 97%
“…Studies that assessed correlation between CV and MTT methods have reported conflicting results. Although some studies found that the CV assay was positively correlated with MTT [67][68][69], other studies did not [70][71][72].…”
Section: Discussionmentioning
confidence: 97%
“…Colorimetric assays are tools that are reasonably simple to perform, very useful for determining yeast viability, and reveal a great association between cellular density and metabolic activity, allowing for semiquantitative evaluation of biofilm formation [ 36 ]. Therefore, to evaluate the metabolic activity of mature C. albicans biofilm, the colorimetric assay (MTT) was carried out according to the method of Prazynska and Gospodarek, 2014 with a few modifications [ 37 ].…”
Section: Methodsmentioning
confidence: 99%